2022
DOI: 10.1101/2022.08.17.504315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure-activity relationship of 2,4-D correlates auxin activity with the induction of somatic embryogenesis in Arabidopsis thaliana

Abstract: 2,4-dichlorophenoxyacetic acid (2,4-D) is a synthetic analogue of the plant hormone auxin that is commonly used in many in vitro plant regeneration systems such as somatic embryogenesis (SE) and organogenesis. The effectiveness of 2,4-D in inducing SE, compared to the natural auxin indole-3- acetic acid (IAA), has been attributed to the stress triggered by this compound rather than its auxin activity. However, this hypothesis has never been thoroughly tested. Here we used a library of 40 2,4- D analogues to te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…These results are in line with our recent observation that SE induction by 2,4‐D primarily requires a strong auxin response that is dependent on the canonical auxin signaling pathway (Karami et al., 2023a). Analysis of the auxin‐responsive reporters pDR5:GUS and pDR5:GFP (Benková et al., 2003; Ulmasov et al., 1997) showed that incubation of IZEs for 7 days on 2,4‐D medium induces a strong auxin response (Figure 1F; Figure S2), especially at the adaxial side of cotyledons on positions where embryonic cell clusters form (Karami et al., 2023b).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…These results are in line with our recent observation that SE induction by 2,4‐D primarily requires a strong auxin response that is dependent on the canonical auxin signaling pathway (Karami et al., 2023a). Analysis of the auxin‐responsive reporters pDR5:GUS and pDR5:GFP (Benková et al., 2003; Ulmasov et al., 1997) showed that incubation of IZEs for 7 days on 2,4‐D medium induces a strong auxin response (Figure 1F; Figure S2), especially at the adaxial side of cotyledons on positions where embryonic cell clusters form (Karami et al., 2023b).…”
Section: Resultssupporting
confidence: 93%
“…Many SE and de novo shoot regeneration protocols make use of the synthetic auxin 2,4‐D to induce SE because of its effectiveness in inducing plant regeneration. Our previous results and the results presented here show that 2,4‐D, as with natural auxins, acts through the canonical auxin response pathway (Karami et al., 2023a) and that the ‘secret’ of 2,4‐D's efficiency lies in it being an inefficient substrate for the auxin efflux machinery (Delbarre eta al., 1996; this work). Due to these properties, 2,4‐D is able to accumulate in the target cells to much higher levels than natural auxins and thus trigger a stronger (optimal) auxin response.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations